Pengaruh Etika Kerja Dan Disiplin Kerja Dengan Kinerja Karyawan Pada Karyawan Taru Martani 1918 Caffe & Resto Yogyakarta - Mutiara; Suji’ah, Uju (Journal of Economics, Business, Accounting and Management, 2025)
The study aims to determine the influence of work ethics and work discipline on employee performance. The sampling technique used saturated sampling with 50 respondents who were employees at Taru Martani Cafe & Resto Yogyakarta. The data collection method used a questionnaire. Instrument testing techniques included validity, reliability, and classical assumption tests. Data analysis techniques used multiple linear regression, coefficient of determination (Adjusted R2), while hypothesis testing used partial significance (t-test), and simultaneous significance (f-test).The results of the study indicate that: 1). Partial significance test: work ethics has a positive but insignificant effect on employee performance variables; work discipline has a positive but insignificant effect on employee performance variables; 2). Simultaneous significance test: work ethics and work discipline have a positive but insignificant effect on employee performance variables. 3). The multiple linear regression equation is Y = 39.360 + 0.045X1 + 0.183X2; The Adjusted R2 value is 0.010, or 1 percent. This indicates that work ethic and work discipline influence employee performance by 1 percent, while the remaining 99 percent is influenced by other factors not examined in this study.